PENGARUH BRAND AWARENESS DAN WORD OF MOUTH COMMUNICATION TERHADAP KEPUTUSAN PEMBELIAN PRODUK KARTU XL AXIATA PADA PT XL AXIATA TBK - haryanto, david; Mulyadi, Mulyadi (Cakrawala Akuntansi & Manajemen, 2024)
The aim of this research is to analyze the influence of brand awareness and word of mouth communication on purchasing decisions for -XL Axiata card products at PT XL Axiata Tbk. In this research, it is predicted that these two variables can measure purchasing decisions for XL Axiata card products. This research uses multiple linear regression analysis. The population in this study were XL Axiata users in the Jakarta area and used 120 respondents as samples in the research. The data collection technique used was nonprobability sampling by distributing online questionnaires. Data were analyzed using the SPSS 29.0 program. The results of this research are that brand awareness and word of mouth communication positively influence purchasing decision